Literature Review: Efektivitas Konsumsi Black Garlic terhadap Penurunan Tekanan Darah pada Penderita Hipertensi - Deffa Ferisa (Lembaga Pengembangan Kinerja Dosen, 2025)
Hypertension, also known as the silent killer, is a serious threat in the world of global health because it causes various vascular diseases to maternal and child mortality during pregnancy. The existence of herb therapy by consuming black garlic has the potential to control and reduce blood pressure. Through this study, it is intended to examine and review the relevant literature and summarized to obtain information about the effectiveness of black garlic consumption on lowering blood pressure in patients with hypertension. The research method uses a literature review based on Google Scholar as a database within the maximum publication range of the last 5 years. The data used is secondary data from previous research results. The results showed that there was a decrease in blood pressure in hypertensive patients after consuming black garlic due to the presence of S-allyl cysteine (SAC), flavonoids, and hydrogen sulfide compounds. Therefore, it has the opportunity to become one of the options in traditional therapy to prevent and treat hypertension conditions.